Jernej B. Kopitar and the Grammar Book of Ignac Kristijanović - Štebih Golub, Barbara (Slavia Centralis, 2020)
In 1837, the last grammar book of Kajkavian literary language Grammatik der kroatischen Mundart was published in Zagreb. In writing his grammar book, I. Kristijanović did not strive for originality; he accepted what he considered useful from all available sources. Since he was impressed by Kopitar’s linguistic knowledge and reputation, Kristijanović was using Kopitar’s Grammatik der Slavischen Sprache in Krain, Kärnten und Steyermark (1808). This paper analyses Kristijanović’s grammar book and tries to identify Kopitar’s influence. It also discusses Kopitar’ review of Kristijanović’s grammar book.